Development of microsatellite markers for Myracrodruon urundeuva (F.F. & M.F. Allemão), a highly endangered species from tropical forest based on next-generation sequencing - Souza, Danilla Cristina Lemos [UNESP]; Rossini, Bruno César [UNESP]; de Souza, Francine Beatriz [UNESP]; Sebbenn, Alexandre Magno; Marino, Celso Luís [UNESP]; de Moraes, Mário Luiz Teixeira [UNESP] (Springer Nature, 2018)
Myracrodruon urundeuva is a tree species of high economic importance due the strength and durability of its wood. Threatened of extinction in Brazil, it is present only in a few forest remnants, mostly in conservation units. Currently, there is little information on the genetic diversity of natural populations in Brazil and even less information about the genome of this species. Here, new species-specific microsatellite loci were developed based on next-generation sequencing (Illumina). More than 100,000 loci were identified in the run, with di- to hexanucleotides motifs. Of these, 20 loci were selected for validation in 30 individuals, with 15 successfully polymorphic loci detected. The number of alleles ranged among loci from 3 to 16, with an average of 7.73, expected (He) and observed (Ho) heterozygosity ranged from 0.246 to 0.902 and from 0.103 to 0.867, respectively. These results point out that these new set of markers has a great potential for use in population genetic studies for genetic conservation of the species.
Keywords: Aroeira; Conservation genetics; Microsatellite; Population genetics